The role of constructive patriotism in the relationship of basic human values and active citizenship for emerging adults in Turkiye - Elban, Mehmet; Aslan, Selcuk (Springernature, 2023)
Active citizenship is closely related to basic human values and patriotism, but empirical studies have lacked investigating these variables holistically. Likewise, the mediating role of patriotism between basic human values and active citizenship seems neglected. In this context, the current study examined the relationships between basic human values, patriotism, and active citizenship by grounding upon basic human values, individualism, and collectivism theories. Results revealed that constructive patriotism positively predicted all dimensions of active citizenship (political literacy, participation and protest, and social responsibility) and mediated the relationships between basic human values and active citizenship. Additionally, while stimulation and self-direction individual values, including motivational goals such as challenges in life, independent thought, and autonomy, were associated with the individual aspect of active citizenship (protest and individual responsibility), the values based on equality (benevolence) were related with the collectivist aspect of active citizenship (participation and social responsibility). One of the most influential findings was that the universalism value could only associate positively with active citizenship through constructive patriotism. Another impressive culture-specific result was that the political literacy dimension of active citizenship was positively related to power, which includes the goal of achieving individual success and dominating others. It can be evaluated as Turkish culture is more of a vertical collectivist because, historically and sociologically, a way of gaining power and status has been possible with politics and its cognitive equivalent, political literacy. The study also revealed that active citizenship is promoted through individual values based upon an individual's independent choices and collectivist values that support societal interests based on equality. In summary, the research mainly revealed that active citizenship is sustained by both individualist values (stimulation, self-direction) and collectivist values (universalism, benevolence), and constructive patriotism has a critical mediating role. Implications of the results were discussed with the relevant literature.
Keywords: Active citizenship; Constructive and blind patriotism; Basic human values; Individual and collectivist values